2008
DOI: 10.1366/000370208786049222
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Imaging with Variable Angles of Incidence Using a Diamond Attenuated Total Reflection Accessory

Abstract: A new development in Fourier transform infrared (FT-IR) imaging using a diamond attenuated total reflection (ATR) imaging accessory in a novel manner that allows the angle of incidence to be varied in order to obtain images from subsurface layers of different thickness is introduced. Chemical images of samples from the same area but with different depths of penetration are obtained by changing the angle of incidence as well as using different spectral bands at different wavenumbers. Changes in the angle of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…It is important to remember that ATR imaging does only produce an image of the surface layer of a tablet, though work has been done to show that these data are still relevant. Recent developments in the area of ATR-FTIR imaging with a variable angle of incidence opens up the opportunity of 3D imaging surface layers of skin in studies of transdermal drug delivery [10] or thin layers of polymeric or pharmaceutical samples [89]. The combination of macro-ATR imaging with mapping [90] offers possibility of obtaining images with large fields of view that may be useful in pharmaceutical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to remember that ATR imaging does only produce an image of the surface layer of a tablet, though work has been done to show that these data are still relevant. Recent developments in the area of ATR-FTIR imaging with a variable angle of incidence opens up the opportunity of 3D imaging surface layers of skin in studies of transdermal drug delivery [10] or thin layers of polymeric or pharmaceutical samples [89]. The combination of macro-ATR imaging with mapping [90] offers possibility of obtaining images with large fields of view that may be useful in pharmaceutical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that it is possible to obtain ATR-FTIR images with higher spatial resolution that can resolve features as small as 12 μm using a diamond ATR accessory with 4x magnification optics. 14,16,17 The same lysozyme protein solution was used in this demonstration and Scheme 1 was applied in this experiment. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Attenuated total reflection (ATR) Fourier transform infrared (FTIR) spectra were collected using a Varian 670 spectrometer (Agilent Technologies, UK) equipped with a Peltier-cooled deuterium tri-glycine sulphate (DTGS), single-element pyroelectric detector. Hydrated beads in buffer were probed by ATR mode using a reflection diamond Golden Gate accessory with optics suitable for spectroscopic imaging (Specac, UK) [ 40 ]. The 45° angle of incidence resulted in the depth of penetration of~1.2 μm at 1600 cm −1 on the diamond’s surface [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%